Roles of the three transcriptional attenuators of the Bacillus subtilis pyrimidine biosynthetic operon in the regulation of its expression. - Lu, Y (1995)
Expression of the Bacillus subtilis pyr operon is regulated by exogenous pyrimidines and the protein product of the first gene of the operon, PyrR. It has been proposed that PyrR mediates transcriptional attenuation at three untranslated segments of the operon (R.J. Turner, Y. Lu, and R.L. Switzer, J. Bacteriol., 176:3708-3722, 1994). In this study, transcriptional fusions of the pyr promoter followed by the pyr attenuation sequences, either individually or in tandem to a lacZ reporter gene, were used to examine the physiological functions of all three attenuators through their ability to affect beta-galactosidase expression. These fusions were studied as chromosomal integrants in various B. subtilis strains to examine the entire range of control by pyrimidines, PyrR dependence, amd developmental control of pyr gene expression. The nutritional regulation of each attenuator separately was roughly equivalent to that of the other two and was totally dependent upon PyrR, and that of tandem attenuators was cumulative. The regulation of a fusion of the spac promoter followed by the pyrP:pyrB intercistronic region to lacZ produced results similar to those obtained with the corresponding fusion containing the pyr promoter, demonstrating that attenuator-dependent regulation is independent of the promoter. Extreme pyrimidine starvation gave rise to two- to threefold-higher levels of expression of a pyr-lacZ fusion that lacked attenuators, independent of PyrR, than were obtained with cells that were not starved. Increased expression of a similar spac-lacZ fusion during pyrimidine starvation was also observed, however, indicating that attenuator-independent regulation is not a specific property of the pyr operon. Conversion of the initiator AUG codon in a small open reading frame in the pyrP:pyrB intercistronic region to UAG reduced expression by about half but did not alter regulation by pyrimidines, which excludes the possibility of a coupled transcription-translation attenuation mechanism. Developmental regulation of pyr expression during early stationary phase was found to be dependent upon the attenuators and PyrR, and the participation of SpoOA was excluded.